Perbandingan Complex Training dan Contrast Training Terhadap Power Otot Tungkai pada Atlet Basket Putra - Ariani Aulia; Alen Rismayadi; Masayu Rizka Risjanna; Patriana Nurmansyah Awwaludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to compare the effectiveness of complex training and contrast training in improving lower-limb muscle strength among male basketball athletes. The study employed a quasi-experimental method with a two-group pretest–posttest design involving eight male athletes from the basketball club of Universitas Pendidikan Indonesia, selected through total sampling. Participants were assigned to two groups using ordinal pairing. Data were analyzed using SPSS, including descriptive statistics, the Shapiro–Wilk normality test, Levene’s test, the Wilcoxon signed-rank test, and the Mann–Whitney U test. The results showed a significance value of Sig. (0.021) < 0.05, indicating a significant difference in the effects of complex training and contrast training on maximum power. The Mann–Whitney U test further revealed a significant difference in performance changes between the two training methods. In conclusion, contrast training produced greater improvements in lower-limb muscle strength compared with complex training. Keywords: Basketball, Lower-Limb Muscle Strength, Complex Training, Contrast Training